2014
DOI: 10.1002/glia.22657
|View full text |Cite
|
Sign up to set email alerts
|

LPS and IL‐1 differentially activate mouse and human astrocytes: Role of CD14

Abstract: Treatment of cultures with toll-like receptor (TLR) ligands or cytokines has become a popular approach to investigate astrocyte neuroinflammatory responses and to simulate the neural environment in various CNS disorders. However, despite much effort, the mechanism of astrocyte activation such as their responses to the TLR ligands and IL-1 remain highly debated. We compared highly pure primary mouse and human astrocyte cultures in their ability to produce proinflammatory mediators (termed “A1”) and immunoregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
126
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(145 citation statements)
references
References 73 publications
13
126
1
2
Order By: Relevance
“…Previous reports have offered conflicting conclusions regarding the expression of CD14 in astrocytes (42)(43)(44)(45). In particular, Tarassishin et al recently reported that mouse astrocytes express CD14 (46). Notably, however, Tarassishin et al passaged primary mouse astrocytes for 6-weeks prior to experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have offered conflicting conclusions regarding the expression of CD14 in astrocytes (42)(43)(44)(45). In particular, Tarassishin et al recently reported that mouse astrocytes express CD14 (46). Notably, however, Tarassishin et al passaged primary mouse astrocytes for 6-weeks prior to experiment.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be established whether this discrepancy is due to the particular experimental conditions employed or whether it reflects species differences. It is noteworthy that some significant functional differences have been described between mouse and human astrocytes (Oberheim et al, 2009;Tarassishin et al, 2014), and differences in gene expression between murine and human astrocytes might also be responsible for their distinct susceptibility to Fxn depletion. A recent analysis of the transcriptome of the prenatal human…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…LPS, the most classic and ancient pathogenic factor, is the main pathogenic factor in Gram-negative bacteria [27]. Endotoxin shock by LPS can induce a series of Fig.…”
Section: Discussionmentioning
confidence: 99%